2008
DOI: 10.1002/bse.630
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility in china: an analysis of domestic and foreign retailers' sustainability dimensions

Abstract: In the past decade, a sizeable body of literature has built up on the concept and characteristics of corporate social responsibility (CSR) in Western countries, where it has also been referred to as sustainability. More recently, attention has grown for CSR in emerging countries. Remarkably, China has hardly been studied so far. This paper aims to help fill this gap by considering, against this background, the CSR notion in China, through an exploration of a small sample of large retailers in China, both Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 23 publications
4
131
0
Order By: Relevance
“…In this context, previous studies have found evidence indicative of the pressures exerted by host-country institutions on MNE subsidiaries' CSR, such as increased local adaptation of their CSR (Barin Cruz and Boehe, 2010;Kolk et al, 2010;Yang and Rivers, 2009). …”
Section: Neo-institutional Theory: Isomorphism and Legitimacymentioning
confidence: 93%
“…In this context, previous studies have found evidence indicative of the pressures exerted by host-country institutions on MNE subsidiaries' CSR, such as increased local adaptation of their CSR (Barin Cruz and Boehe, 2010;Kolk et al, 2010;Yang and Rivers, 2009). …”
Section: Neo-institutional Theory: Isomorphism and Legitimacymentioning
confidence: 93%
“…In addition, we offered respondents the option to indicate that they had no idea. 4 As an exploratory extension, we included items on environmental and labour/workforce responsibility, as these have been mentioned to be of increasing importance to Chinese consumers and in the evaluation of domestic versus foreign firms (French, 2010a(French, , 2010bKolk et al, 2010;Lin, 2010;Zhou et al, 2012;cf. Xu and Yang, 2010).…”
Section: Sample and Methodologymentioning
confidence: 99%
“…These two topics were also mentioned to be of increasing importance to Chinese consumers and to the evaluation of domestic versus foreign firms in other publications, but left unexplored (French, 2012a(French, , 2012bKolk et al, 2010;Zhou et al, 2012).…”
Section: Differences In Csr Expectations For Local Versus Foreign Firmsmentioning
confidence: 99%
See 2 more Smart Citations